2021 IEEE Conference on Antenna Measurements &Amp; Applications (CAMA) 2021
DOI: 10.1109/cama49227.2021.9703640
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning System of UAV for Antenna Beam Localization

Abstract: Along with the growth of satellite communication industry, the demands and benefits to perform satellite terminal antenna evaluation are increasing. UAV based in-situ measurement can increase the efficiency of the measurement procedure. Main beam localization is a necessary procedure to execute the antenna evaluation test. To accelerate the process of finding the antenna beam centre, this paper develop a meta-reinforcement learning based algorithm. The developed algorithm is compared with other methods and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Overall, it can be concluded that the EI acquisition function with restricted sampling is the most optimal configuration for peak detection with respect to lowest localization error using Bayesian optimization. Recent novel approach is proposed in [9], where the authors used recurrent neural networks for antenna man beam localization. However, this approach requires training the algorithm based on a specific antenna's radiation pattern and does not provide a more generic solution to this problem.…”
Section: A Main Beam Localizationmentioning
confidence: 99%
“…Overall, it can be concluded that the EI acquisition function with restricted sampling is the most optimal configuration for peak detection with respect to lowest localization error using Bayesian optimization. Recent novel approach is proposed in [9], where the authors used recurrent neural networks for antenna man beam localization. However, this approach requires training the algorithm based on a specific antenna's radiation pattern and does not provide a more generic solution to this problem.…”
Section: A Main Beam Localizationmentioning
confidence: 99%